2008
DOI: 10.1007/s00247-008-1080-x
|View full text |Cite
|
Sign up to set email alerts
|

Harmonic voiding urosonography with a second-generation contrast agent for the diagnosis of vesicoureteral reflux

Abstract: VUS HI and a second-generation contrast agent improved the identification of reflux in children. Our data reveal a higher sensitivity of the method compared to VCUG. Thus it can be used as an alternative radiation-free imaging method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
75
1
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(86 citation statements)
references
References 34 publications
3
75
1
7
Order By: Relevance
“…As the VUR is a real-time radiation free technique and the switch from one kidney to contralateral is extremely rapid, the continuous exploration without any pauses captures a higher number of refluxes in both sides. Many authors consider that the VUS with a second-generation contrast agent is superior to conventional fluoroscopic cystography in the detection and grading of VUR [3,5,13]. In addition, the absence of major side effects and low incidence of minor side effects such as dysuria, -not related to the contrast agent, but rather to bladder catheterization-are definite advantages [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the VUR is a real-time radiation free technique and the switch from one kidney to contralateral is extremely rapid, the continuous exploration without any pauses captures a higher number of refluxes in both sides. Many authors consider that the VUS with a second-generation contrast agent is superior to conventional fluoroscopic cystography in the detection and grading of VUR [3,5,13]. In addition, the absence of major side effects and low incidence of minor side effects such as dysuria, -not related to the contrast agent, but rather to bladder catheterization-are definite advantages [14].…”
Section: Discussionmentioning
confidence: 99%
“…Combined use with tissue harmonic imaging that has a high sensitivity for contrast agent [1,2] has improved the diagnostic accuracy of this method, which is nearly 100% in the most recent case studies [3]. VUS, as the standardized technique, is used to acquire information during the bladder filling and voiding phase [4][5][6][7]. However, the voiding phase, especially in older children, creates both psychological and management problems.…”
Section: Introductionmentioning
confidence: 99%
“…The second generation of ultrasound contrast agents (UCA) and higher quality ultrasound machines, with contrast-specific software technology, have allowed the application of ceVUS without ionizing radiation (15). ceVUS has become a routine method in the diagnosis of VUR in many European centres, because in recent years there is higher awareness of the potential harmful effects of exposure to ionizing radiation in diagnostic imaging procedures in children (15)(16)(17)(18)(19)(20)(21)(22)(23). Kis et al (25) reported ceVUS to be more sensitive than VCUG since it is a real time imaging method, allowing prolonged, continuous scanning, and thus has the potential to detect intermittent VUR (24).…”
Section: Contrast-enhanced Voiding Urosonographymentioning
confidence: 99%
“…The procedure also involves tissue harmonic imaging, which is based on the phenomenon of non-linear distortion of the acoustic signal as the ultrasound wave insonates and travels through the body tissues. It improves contrast and spatial resolution, and reduces artefacts when compared to conventional grayscale ultrasound (38,39). Together with the subtraction technique, the contrast-specific harmonic imaging mode further increases the conspicuity of the microbubbles.…”
Section: Contrast-enhanced Voiding Urosonographymentioning
confidence: 99%
See 1 more Smart Citation